Factors affecting job satisfaction in two automotive industries in Malaysia - Dawal, Siti Zawiah; Taha, Zahari (Penerbit UTM Press, 2006)

(untitled)
Survey Was Conducted To Investigate The Relationship Between Job Satisfaction, Job Characteristics And Environmental Factors That Affect Work Design In Two Automotive Manufacturing Companies In Malaysia. The Aim Of The Study Is To Determine The Factors That Influence Employees’ Perception Towards Their Work. 170 Male Subjects Between The Ages Of 18 To 40 Years With The Mean Age Of 26.8 And Standard Deviation (Sd) Of 5.3 Years And Mean Work Experience Of 6.5 And Sd Of 4.9 Years Were Involved. A Set Of Multiple Choice Questionnaire Was Developed And Data Was Collected By Interviewing The Employees At The Production Plants. The Survey Focused On Job Satisfaction, Job Characteristics And Environmental Factors. The Results Showed That Job Characteristics And Environmental Factors Were Significantly Related To Job Satisfaction.